Gestão do comportamento informacional apoiada na cultura organizacional e em modelos mentais - Cavalcante, Luciane de Fátima Beckman [UNESP] (2010)
The information and the individuals pass all tasks and process organizational is possible direct studies to the organizational context, in what understand and identify the way as the individuals work the information. Is relevant understand like the individual develops certain behaviors regarding the information, what implies in do an analysis this organizational actor under an cognition approach, because the informational behavior triggered by him can derive from process and representations presents in the individual mind. To present research aimed at analyze, in a cellulose manufacturing company, the relation between the individuals informational behavior and the TICs, focusing cognitions aspects that triggered such behavior, as the mental models, with objective of to propose a systemization to the managment of informational behavior returned to the technologies of information and communication applied to the business environments. To research was supported by twenty participants of distinct organizational levels of a cellulose manufacturing company in the São Paulo State. The methodological procedures were supported by the Laurence Bardin method, called 'Content Analysis', more specifically applying the technical 'Categories Analysis'. Were elaborate and utilized as data collecting instrument, the structured questionnaire and the structured interview. The results obtained provided to identify the individual mental representations that the researched possess about the informational behavior informacional, and understand how the organizational culture / informational culture can interfere in that behavior. It was possible verify, also, that the research individuals participants conceive the TICs as a tool that helps the activities developed in the company, motivating the way as the information flowed in the organizational environment. Believes that the arguments... (Complete abstract click electronic access below)